Status Gizi sebagai Faktor Risiko Mortalitas di Rumah Sakit pada Pasien Lanjut Usia Pasca Reseksi Tumor Kolorektal - Wulandari, Ayu Fitri Sekar; Budiono, Parish; Mupangati, Yudo Murti (UI Scholars Hub, 2025)
Introduction. Malnutrition in elderly patients, particularly those with colorectal cancer, increases morbidity, mortality, and length of hospital stay due to metabolic dysregulation and hypermetabolic perioperative response, affecting wound healing, infection risk, postoperative complications, and nutritional deficits. This study aimed to analyze whether nutritional status is a risk factor for in-hospital mortality in elderly patients after colorectal tumor resection. Methods. A case-control matching study was conducted on elderly patients who underwent colorectal tumor resection, using secondary data from elderly inpatients at Dr. Kariadi General Hospital from January 2020 to April 2024. The collected data were analyzed using bivariate analysis with the Chi-square test and multivariate analysis with logistic regression. Results. The study involved 48 elderly patients who died during treatment and 48 elderly patients who survived until the end of treatment. Nutritional screening assessed with Skrining Gizi Kariadi (SGK) was not associated with in-hospital mortality after colorectal tumor resection [p=0.306; OR 1.952 (95% CI 0.694-5.491)]. However, nutritional assessment based on American Society for Parenteral and Enteral Nutrition (ASPEN) criteria was associated with in-hospital mortality after colorectal tumor resection [p<0.001; OR 5.800 (95% CI 2.345-14.344)]. The results of the multivariate analysis also revealed a significant link between nutritional status based on the ASPEN criteria (p=0.028) and a higher risk of in-hospital mortality in elderly patients after colorectal tumor resection. Conclusion. Nutritional status, based on ASPEN criteria, is a risk factor for in-hospital mortality in elderly patients after colorectal tumor resection.